Construction of a Framework for Selecting an Effective Learning Procedure in the School-Level Sector of Online Teaching Informatics - Andi, Hari Krishnan (Journal of Ubiquitous Computing and Communication Technologies, 2022)
Currently, there is no way soon to stop the coronavirus epidemic that has spread over the globe. People are alarmed by its quick and widespread expansion. COVID-19’s transmission chain was then broken by everyone. There was a gradual decrease in social and physical closeness. Distancing yourself from others is a way to prevent the transmission of disease. The purpose of this research is to investigate how online learning can be implemented in Tamil Nadu, India, during the COVID-19 epidemic. This research works focuses to find efficient learning procedure in eLearning protocols. The findings indicated that Google Classroom, WhatsApp, and Zoom Clouds Meeting were consecutively the most commonly utilized programs to help in remote learning. Despite this, most instructors continue to use the learning paradigm while teaching in virtual environments. Online learning and remote education are the most common methods of learning. The instructor claims that the learning model used is beneficial to their work in creating a virtual classroom since it adheres to the model’s structured grammar. The experimental test has been conducted with 125 students who anonymously filled out a questionnaire and voted for more visual based eLearning. The findings show that students in distance education believed that there were more tasks than in face-to-face education. At the same time, students indicated that they spent more time studying at home than in school.